2019
DOI: 10.3126/nelta.v24i1-2.27681
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to ICT use in EFL teacher education courses in Nepal: An activity theory perspective

Abstract: The effectiveness of pre-service teachers’ ICT training during teacher education course is often linked with the teacher educators’ (TEs’) practices. TEs’ digital practices, however, are under-studied, thus, are not fully understood. This study, which draws on the theoretical tenets of Activity Theory, reports on the factors that limit TEs’ digital practices in a context where technology use has just begun to evolve. Using a multi-method case study, this study collected data from EFL TEs and policymakers. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
37
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(40 citation statements)
references
References 15 publications
3
37
0
Order By: Relevance
“…Delivering learning to homes has been challenging to teachers in most under-resourced contexts, where the accessibility, availability, and use of technology in education are not widespread (Khan et al, 2012 ). Apart from this, teachers’ poor digital skills prevent them from delivering effective learning (Laudari & Maher, 2019 ), and little thought has been given to train them on how to manage students' social, physiological, and psychological issues. While higher education institutions have generally managed to implement teaching and learning activities using online tools globally, the systems and resources in developing countries such as Bangladesh and Nepal are inadequate (Dawadi et al, 2020 ; Uddin, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Delivering learning to homes has been challenging to teachers in most under-resourced contexts, where the accessibility, availability, and use of technology in education are not widespread (Khan et al, 2012 ). Apart from this, teachers’ poor digital skills prevent them from delivering effective learning (Laudari & Maher, 2019 ), and little thought has been given to train them on how to manage students' social, physiological, and psychological issues. While higher education institutions have generally managed to implement teaching and learning activities using online tools globally, the systems and resources in developing countries such as Bangladesh and Nepal are inadequate (Dawadi et al, 2020 ; Uddin, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Using ICT in higher education has been increasingly common since the advent of the Internet, though the degree of its use differs from one context to another. A plethora of research claims that digital technology meets not only the changing need of higher education students, but it also enhances learning (Alzahrani & Seth, 2021 ; Becker, 2017 ; Du Toit & Verhoef, 2018 ; Lai, 2011 ; Laudari & Maher, 2019 ; Underwood, 2009 ; Waghid & Waghid, 2016 ). Lai ( 2011 ) and Underwood ( 2009 ), for example, assert that technology is used in all higher education institutions, though to varying degrees, to support traditional forms of teaching.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This view proclaimed by the participants shows that with limited ICT tools and devices, it is difficult to integrate ICT in their teaching learning frequently (Cunningham, 2015). Similarly, Laudari and Maher's (2019) studies also revealed that lack of infrastructures hinder ICT integration in ELT. Mishra and Koehler (2006) highlighted that instructors' technical competencies are not enough for ICT integration so they need technical resources.…”
Section: Challenges Of Ict Integrated Teachingmentioning
confidence: 93%
“…However, Cunningham's (2015) study in Kenya explored that institutional policies, ICT training to teachers, infrastructures and lack of context suitable E-content as hindrance of technology integration. In this line, Laudari and Maher's (2019) study in Nepal explored that physical infrastructure and resources as the barriers in the use of ICT. Their studies also explored physical infrastructure and resources, institutional policies and lack of ICT training to teachers as barriers in ICT integration in ELT.The aforementioned reviewed research studies on English teachers' perceptions and practices of integrating ICT in ELT explored effects, benefits and the barriers of ICT in home and abroad.…”
Section: Ict Integration In Teaching and Learning Englishmentioning
confidence: 99%